The art of agile development - Shore, James; Larsen, Diana; Klitgaard, Gitte; Warden, Shane (Theory in practice (Sebastopol, Calif.), 2021)
"Most companies developing software employ something they call "Agile." But there's widespread misunderstanding of what Agile is and how to use it. If you want to improve your software development team's agility, this comprehensive guidebook's clear, concrete, and detailed guidance explains what to do and why, and when to make trade-offs. In this thorough update of the classic Agile how-to guide, James Shore provides no-nonsense advice on Agile adoption, planning, development, delivery, and management taken from over two decades of Agile experience. He brings the latest ideas from Extreme Programming, Scrum, Lean, DevOps, and more into a cohesive whole. Learn how to successfully bring Agile development to your team and organization--or discover why Agile might not be for you."--Amazon.com.